Art, another vision for technological mediation in E-Learning - Elenes, Evelyn (IJRDO- Journal of Educational Research, 2018)
This article works on the construction of the Pattern Language from the perspective of art. For this, I link the Duchamp's Large Glass and my author's own experience as a visual artist, to finally demonstrate that Patterns Language is not the only valid one for the production of knowledge, this from the demonstration of the work of John Nash captured by the book, A beautiful mind by Silvia Naser. This article is one of the products of the main source of research in Postdoctoral Stay, Friendship Politics.